Anti-Inflammatory Activity of Copao (Eulychnia Acida Phil., Cactaceae) Fruits - Jiménez Aspee, Felipe (2015)
Copao (Eulychnia acida Phil., Cactaceae) is an endemic species occurring in northern Chile. The edible fruits of this plant are valued for its acidic and refreshing taste. Phenolic-enriched extracts from copao fruit pulp and epicarp, collected in the Elqui and Limari river valleys, were assessed by its in vitro ability to inhibit the pro-inflammatory enzymes lipoxygenase (LOX) and cyclooxygenases (COX-1 and COX-2). At 100 μg/mL, pulp extracts showed better effect towards LOX than epicarp extract, while COX-2 inhibition was observed for both epicarp and pulp samples. In general, the extracts were inactive towards COX-1. A positive correlation was observed between the anti-inflammatory activity and the main phenolic compounds found in this fruit. Copao fruits from the Limari valley, a main place of collection and commercialization, showed major activity, adding evidence on the possible health-beneficial effects of this native Chilean fruit.